Corrientes litorales en el sector de la boquilla, cartagena (colombia) (1984)
Current measurements were made at La Boquilla Beach using small floats joined by a nylon thread to bottles partially filled with sea water.   Within a beach lenght of about 1.500 m, three well defined groups of currents having different orientations were identified.  The observed current system does not fit in the models of nearshore circulation traditionally accepted. This may indicate that nearshore circulation and its associated sediment transport processes are not completely understood and that more research is required on the subject.